African Private Higher Education: Progressive Policies and Ambivalent Stances - Tamrat, Wondwosen; Teferra, Damtew (International Higher Education, 2018)
As the global and regional thirst for higher education continues to surge, it is time to think how private higher education institutions (PHEIs) can be groomed to play their roles within an evolving higher education landscape. It is imperative to put in place appropriate policies and legislations, for these institutions to play a key role in socioeconomic development. This article outlines various progressive PHE policies and legislations across Africa and examines their importance in enhancing the growth of the sector.